(3caGjg GdJYdje aj eYQag hVY GdJbhjes - (3CMeO Hf ZdGe Gddg Gdche GdQjTis; (3Gdche GdQjTj , CMeO Hf ZdGe Gddg Hf CMeO Hf eMeO, TgGH GdOjf,J (B836 (3g` s
(3ChdgG (B:s
(3agPg ebOeg dWjag VefJgG fcJG TQjag JTJed Ydi eYQag GSJNQGL GdJbhje ef cJGHi GdeSei HGddeYg ai Md GdchGcH GdSHYg s
(3BNQgG (B:s
(3NGQLkG YeG jJNdd Pdc ef GdC(B'(3eGd hMSGH GdcShaGJ hGdNShaGJ haUhd GdSfg hGdSgGe hGdRQLjg heOGNdI GdTghQ hWdhY GdTYQ hZjQ Pdc s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B192 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B39s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B89 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B977(1)) s
Keywords: (3Gdadcs